The Cultural Lens Approach to Bowen Family Systems Theory: Contributions of Family Change Theory. Issue 2 (30th April 2018) - Erdem, Gizem; Safi, Ommay Aiman
Abstract: An accumulation of theoretical and empirical work focuses on expanding Bowen family systems theory (BFST) to be more culturally expansive by including gender, ethnicity, race, social class, and sexual orientation, as well as family history, values, and rituals. In the current article, we contribute to the discussion of culture in BFST and move the question of diversity from how family processes are different to why they are different. Utilizing Hardin and colleagues' cultural lens approach, we discuss the cultural validity of BFST, more specifically the concept of differentiation of self and its premises, in five steps. Further, we propose the integration of Kağıtçıbaşı's family change theory and Carter and McGoldrick's multicultural perspective with BFST and offer cultural examples. Potential contributions and limitations of the cultural lens approach in expanding our understanding BFST are discussed, as are implications for research and clinical practice.